INFLUENCE OF FAMILY DYNAMICS ON STUDENTS’ BEHAVIOR: CHALLENGES AND OPPORTUNITIES - Billanes, Freddie B. (Proceeding of the International Conference on Family Business and Entrepreneurship, 2024)
Family dynamics impact comfort and happiness. 801 students were surveyed using a descriptive correlational study and 0.897-reliable researcher-made questionnaire. The study found that open communication, quality time, respect, responsibility, and supporting a peacemaker during tough times strengthened family ties. Parental honesty and dependability were closest. Most families have money and work-life issues. Number of children, family members' traits, parents' connection, and gentle or hard upbringing affected family dynamics. Family relationships are less impacted by the "mix" of people in a family, others' influence, and life events such an affair, divorce, trauma, unemployment, homelessness, an absent parent, or a chronically ill or disabled child Spending meals with the family, feeling like their family supports their objectives, enjoying family activities, feeling like they would still prefer growing up in their family, and asking their parents for help were most essential. Being closer to extended family than their own, mediating rather than leading healthy family relations, and seeking professional family help were the least common. Family issues should be matched with academic chances, says study. They value family, self-drive, and academics. Reclaiming a habit garnered family support, but downplaying the risk to their schooling and addressing cultural differences in extended families that may create problems was neglected. Family dynamics shaped students' behavior, including prioritizing family needs and interests over personal matters, showing concern for parents and other family members, offering support in any way possible, solving family problems, using a strength-based approach to help family members cope with difficult situations, responding to family-related comments, and trusting Minor issues reduce sibling strife. They use family strengths to tackle problems. Though connected, family factors like sex and money affected student behavior differently at home and school. A number of traits and ties were similar.